2004
DOI: 10.1038/sj.ijo.0802826
|View full text |Cite|
|
Sign up to set email alerts
|

Association of leptin levels with obesity and blood pressure: possible common genetic variation

Abstract: OBJECTIVE: To ascertain the extent to which relationships between obesity (OB) and blood pressure (BP) can be explained by an individual's leptin plasma levels. DESIGN: Pedigree-based cross-sectional study in an apparently healthy population of European origin. SUBJECTS: The study sample is comprised of 90 nuclear and more complex families totaling 210 male and 213 female subjects aged 18-75 y, randomly recruited in Bashkorstan Autonomic region, Russia. MEASUREMENTS: Various fatness and fat distribution traits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 36 publications
2
25
0
Order By: Relevance
“…There also may be common effects not accounted for by shared genes, such as insulin affecting sympathetic activity and thus Genetic influences on body fat and blood pressure TL Nelson et al increasing blood pressure. 37 A recent study by Livshits 38 found among families that correlations between blood pressure and obesity were mediated by leptin. They also found that the familial effects on body fat and blood pressure were totally gone after controlling for leptin, suggesting that genetic variation in body fat and blood pressure is due to genetic variation of leptin.…”
Section: Discussionmentioning
confidence: 99%
“…There also may be common effects not accounted for by shared genes, such as insulin affecting sympathetic activity and thus Genetic influences on body fat and blood pressure TL Nelson et al increasing blood pressure. 37 A recent study by Livshits 38 found among families that correlations between blood pressure and obesity were mediated by leptin. They also found that the familial effects on body fat and blood pressure were totally gone after controlling for leptin, suggesting that genetic variation in body fat and blood pressure is due to genetic variation of leptin.…”
Section: Discussionmentioning
confidence: 99%
“…Acute, resistance exercise has been reported to have no impact (Livshits et al, 2005;Fenkci et al, 2006;Konstantinides et al, 2001;Franklin, 2005;Rahmouni et al, 2004;Altman, 2003) or to decrease plasma leptin levels in these studies (Mendosa-Nunez et al, 2002). After 20 weeks of training a decrease in leptin levels was observed in men, but only if decreases in body fat occurred (Franklin, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It also suppresses appetite through acting on the hypothalamus (Mokdad et al, 2003;Ronti et al, 2006;MendosaNunez et al, 2002). In recent years, leptin has been reported to increase arterial pressure and heart rate by peripherally or centrally mediated mechanisms (Livshits et al, 2005;Franklin 2005;Rahmouni and Haynes 2004). The finding that leptin is linked to heart-disease risk independently from C-reactive protein (CRP), an inflammation marker, strongly suggests that fat may be important in heart-disease risk (Altman 2003;Canavan et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review concluded the existence of an association between depression and type 2 diabetes (Musselman et al, 2003). Furthermore, it has been shown that several hormones such as cortisol, an index of hypothalamic-pituitary-adrenal (HPA) axis activity and leptin, an adiposity hormone involved in food intake and weight regulation, have been involved in the regulation of mood and metabolic function (Atmaca et al, 2005;Bjorntorp, 2001;Kraus et al, 2001;Liuzzi et al, 1999;Livshits et al, 2005). Despite the consistent overlap between these two traits, few studies have adopted an integrative strategy that includes both psychological and physiological assessments to elucidate the etiology of anxiety/depression and metabolic functions.…”
mentioning
confidence: 99%